A comparative study on the political awareness and level of trust to the government in relation to the level of political participation of in-school and out-of-school youths in Miag-ao, Iloilo. - Baylosis, Jericho Alain G
This study sought to determine, compare, and analyze the political awareness and the level of trust to the government in relation to the level of political participation of the in-school and out-of-school youth in Miag-ao. Specifically the study tried to identify the political awareness of both in-school and out-of-school youth and the factors that influence their political awareness. It likewise sought to determine the differences in the political awareness, level of trust to the government, and the level of political participation in-school and out-of school youth. The study also sought to find out if the level of trust to the government affects the level of political participation of the respondents . One-hundred three (103) in-school youth were selected by simple random sampling from Miag-ao National High School and twenty-one (21) out-of-school youth were selected by employing the snowball sampling from the barangays that compose the poblacion area of the municipality of Miag-ao served as the respondents of the study., Likert scale used to measure the respondents' level of trust to the government and level of political particiaption. On the other hand, a "yes-no scale" was used to measure the political awareness of both respondents. The Mann-Witney Non Parametric test and the Chi-square test were used to analyze the results of the study. Research results showed that age does not affect the political awareness of the respondents but on the other hand, results of the study also showed that sex and educational attainment affect the respondents' political awareness and that these two factors serve as a determinant of political awareness. Comparing the results of both in-school and out-of-school youth showed both sets of respondents are politically aware, for their averages fall above the 50 line but the in-school youth showed a higher level of political awareness as compared to the out-of-school youth. In terms on their level of trust to the government, both respondents are undecided if they trust the government. Research results from the level of political participation of the in-school and out-of-school youth showed that both respondents agree that the youth should be politically participate. Lastly the results of the study showed that the respondents' level of trust to the government does not affect their level of political participation.